Assessing the long-term in vivo degradation behavior of magnesium alloys - a high resolution synchrotron radiation micro computed tomography study - Sefa, Sandra; Wieland, D.C. Florian; Helmholz, Heike; Zeller-Plumhoff, Berit; Wennerberg, Ann; Moosmann, Julian; Willumeit-Römer, Regine; Galli, Silvia (Frontiers in Biomaterials Science, 2022)
Biodegradable magnesium (Mg) implants are emerging as a potential game changer in implant technology in situations where the implant temporarily supports the bone thereby avoiding secondary surgery for implant removal. However, the consequences of the alteration in the degradation rate to bone healing and the localization of degradation and alloying products in the long term remains unknown. In this study, we present the long-term osseointegration of three different biodegradable Mg alloys, Mg-10Gd, Mg-4Y-3RE and Mg-2Ag, which were implanted into rabbit femur for 6 and 9 months. In addition, we have investigated the effect of blood coating on the in vivo performance of the aforementioned alloys. Using high-resolution synchrotron radiation based micro computed tomography, the bone implant contact (BIC), bone volume fraction (BV/TV) and implant morphology were studied. The elemental traces have been characterized using micro X-ray fluorescence. Qualitative histological evaluation of the surrounding bone was also performed. Matured bone formed around all three implant types and Ca as well as P which represent parts of the degradation layer were in intimate contact with the bone. Blood coating significantly improved BIC in Mg-2Ag screws at 6 months. Despite different implant degradation morphologies pointing toward different degradation dynamics, Mg-10Gd, Mg-4Y-3RE and Mg-2Ag induced a similar long-term bone response. Importantly, RE elements Gd and Y used in the alloys remained at the implantation site. Consequently, we have shown that short and medium-term in vivo degradation rates do not represent indicators for long-term osseointegration of Mg-based implants.